A universal standard for the validation of blood pressure measuring devices: Association for the Advancement of Medical Instrumentation/European Society of Hypertension/International Organization for Standardization (AAMI/ESH/ISO) Collaboration Statement. Issue 3 (March 2018) - Stergiou, George S.; Alpert, Bruce; Mieke, Stephan; Asmar, Roland; Atkins, Neil; Eckert, Siegfried; Frick, Gerhard; Friedman, Bruce; Graßl, Thomas; Ichikawa, Tsutomu; Ioannidis, John P.; Lacy, Peter; et al.
Abstract : N/A: In the last 30 years, several organizations, such as the US Association for the Advancement of Medical Instrumentation (AAMI), the British Hypertension Society, the European Society of Hypertension (ESH) Working Group on Blood Pressure (BP) Monitoring and the International Organization for Standardization (ISO) have developed protocols for clinical validation of BP measuring devices. However, it is recognized that science, as well as patients, consumers and manufacturers would be best served if all BP measuring devices were assessed for accuracy according to an agreed single validation protocol that had global acceptance. Therefore, an international initiative was taken by AAMI, ESH and ISO experts who agreed to develop a universal standard for device validation. This statement presents the key aspects of a validation procedure, which were agreed by the AAMI, ESH and ISO representatives as the basis for a single universal validation protocol. As soon as the AAMI/ESH/ISO standard is fully developed, this will be regarded as the single universal standard and will replace all other previous standards/protocols.